2006
DOI: 10.1111/j.1540-8167.2006.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Serial Cardioversion by Class IC Drugs During 4 Months of Persistent Atrial Fibrillation in the Goat

Abstract: The progressive loss of efficacy of Class IC drugs to cardiovert AF of longer duration is not due to a decrease in the sensitivity of remodeled atrial myocardium for Class IC drugs. Failure of cardioversion was due to an increase in the critical AF cycle length required for pharmacological cardioversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…These observations suggest that factors that reduce APD, thereby increasing the angular velocity and functional anchoring of rotors, should reduce the ability of Na ϩ channelblocking drugs to terminate AF. This has, in fact, been the clinical observation with AF-related electrical remodeling, which both reduces APD and induces resistance to Na ϩ channel blocker-induced AF termination (7,39).…”
Section: Interactions Among Ach Concentrations/distributions and Tissmentioning
confidence: 95%
“…These observations suggest that factors that reduce APD, thereby increasing the angular velocity and functional anchoring of rotors, should reduce the ability of Na ϩ channelblocking drugs to terminate AF. This has, in fact, been the clinical observation with AF-related electrical remodeling, which both reduces APD and induces resistance to Na ϩ channel blocker-induced AF termination (7,39).…”
Section: Interactions Among Ach Concentrations/distributions and Tissmentioning
confidence: 95%
“…Of note, V 0.5 of I Na inactivation is shifted by +10 mV in cells isolated from AF versus sinus rhythm patients,46 which may reduce the sensitivity to I Na blockers. The potency of Class IC agents appears not to be altered by atrial remodeling in goats 47. Thus, there are many possible permutations that could develop with disease states that could affect the atrial selectivity of sodium channel blockers.…”
Section: Unanswered Questionsmentioning
confidence: 99%
“…12 In parallel, the success rate of pharmacological cardioversion decreases until it is no longer possible to cardiovert AF in most goats (permanent AF). 13 To investigate the transition from persistent to permanent AF, we have studied goats after 3 weeks of maintained AF (short-term AF [ST]) and goats after 6 months of AF (long-term AF [LT]). We characterized conduction patterns in the atrial free walls during pacing and AF using high-resolution epicardial mapping and a new method to describe fibrillation patterns.…”
Section: Clinical Perspective On P 599mentioning
confidence: 99%
“…Eijsbouts et al 13 showed that the cardioversion efficacy of flecainide gradually decreases from 60% after 1 month to 17% after 4 months of AF. In another study, we reported a 100% success rate of cardioversion with a combination of AVE0118 and dofetilide in goats after 46Ϯ17 days of AF.…”
Section: Time Course Of Af Stabilizationmentioning
confidence: 99%